Status and development trends of research on CO2 decompression characteristics and crack propagation - Buze YIN; Weihe HUANG; Qing MIAO; Feng YAN; Xin OUYANG; Qihui HU; Guangchun SONG; Yuxing LI (You-qi chuyun)
Pipelines are suitable for long-distance and high-volume transportation and thus become the key link of Carbon Capture, Utilization and Storage (CCUS) technology to connect the carbon sources and sinks. However, due to the special decompression characteristics of CO2, continuous crack propagation is highly likely to occur in long-distance CO2 pipelines after leakage during the operation. Thus, the research status on the leakage-induced decompression characteristics and crack propagation of CO2 pipelines at home and abroad was comprehensively reviewed from the three aspects of the test, theoretical research and numerical simulation. Then, summarization was made for the adaptability of different equations of state, impurity factors and theoretical models to the leakage-induced decompression characteristics, as well as the test results of leakage-induced decompression in different scales, initial conditions, phase states, impurity contents and leakage modes. On this basis, the effects of different phase states, initial conditions, pipe materials, impurity contents and types on crack propagation were analyzed. Besides, a comparison was performed for different theoretical models of crack propagation in CO2 pipelines and their application scope, as well as the numerical simulation methods for crack propagation and fluid–structure interaction. Finally, a prospect was made for the contents to be further researched in an urgent way, so as to provide references to the research on CO2 pipeline leakage and crack propagation in China, thereby facilitating to improve the CCUS technology level for safety guarantee.